2010
DOI: 10.1086/657045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seasonality on Brain Size Evolution: Evidence from Strepsirrhine Primates

Abstract: Seasonal changes in energy supply impose energetic constraints that affect many physiological and behavioral characteristics of organisms. As brains are costly, we predict brain size to be relatively small in species that experience a higher degree of seasonality (expensive brain framework). Alternatively, it has been argued that larger brains give animals the behavioral flexibility to buffer the effects of habitat seasonality (cognitive buffer hypothesis). Here, we test these two hypotheses in a comparative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
84
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 67 publications
11
84
1
1
Order By: Relevance
“…Recent studies suggest that the costs of evolutionary brain enlargement were overcome by a permanent increase in net energy intake (8,9), renewing interest in the role of ecological complexity in brain size evolution (1,4,6). To our knowledge, our study provides the first clear example of a future-oriented cognitive ability used in a food-scarce period within a highly competitive tropical forest environment that could enable all large-brained foragers to buffer drastic declines in food availability.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Recent studies suggest that the costs of evolutionary brain enlargement were overcome by a permanent increase in net energy intake (8,9), renewing interest in the role of ecological complexity in brain size evolution (1,4,6). To our knowledge, our study provides the first clear example of a future-oriented cognitive ability used in a food-scarce period within a highly competitive tropical forest environment that could enable all large-brained foragers to buffer drastic declines in food availability.…”
Section: Discussionmentioning
confidence: 77%
“…With recent comparative studies on brain size evolution, the role of the temporal availability of food sources has gained renewed attention (8,9). These studies are built on the idea that additional neural tissue should not only be functional, but an animal must have sufficient energy to afford it (10,11).…”
mentioning
confidence: 99%
“…Thus, when periods of unavoidable food scarcity recur, we expect most species to be forced to evolve smaller brains than their sister taxa in less seasonal environments. Indeed, we found that seasonality in food (and hence energy) intake is negatively correlated with brain size in strepsirrhine and catarrhine primates (van Woerden, van Schaik, and Isler 2010;van Woerden et al 2012) as predicted by the expensive brain framework. Work on birds, however, had earlier suggested that habitat Source.…”
mentioning
confidence: 68%
“…Cognitive buffering of fluctuations in food availability, such as the flexible switching between different resources, may be impossible where seasonality is too severe. Thus, lemurs may be condemned to be small-brained due to the presence of an extreme lean season in Madagascar, with the telling exception of the large-brained aye-aye, which extracts larvae from wood and experiences virtually no seasonality [40]. Second, predation may be unavoidable for small species that have many large predators.…”
Section: Net Increase In Energy Inputmentioning
confidence: 99%